Hubungan Persentase Visceral Fat dengan Tekanan Darah pada Pasien DM Tipe II di RS Haji Medan - Adetya, Intan Tiara; Lufiana, Fardella (Buletin Farmatera, 2025)
Abstract: Diabetes mellitus is a metabolic disorder with chronic hyperglycemia due to genetic and lifestyle interactions. Type 2 diabetes and hypertension are often comorbidities because they share risk factors such as endothelial dysfunction, vascular inflammation, atherosclerosis, dyslipidemia, and obesity. Increased blood pressure in diabetics is triggered by hyperinsulinemia, insulin resistance, and sleep apnea. Visceral fat also plays an important role in the development of hypertension, especially in adulthood. This study aims to determine the relationship between visceral fat percentage and blood pressure in Type II DM patients at Haji Medan Hospital The research conducted was observational analytical research with a cross sectional approach. The largest age group is 50–59 years old and the most gender is male (53.6%). The most blood pressure category is grade I hypertension (50.7%), and the most visceral fat category is high (10–14%). Systolic blood pressure had an average value of 142.4 mmHg, diastolic 81.8 mmHg, and MAP 102 mmHg. The correlation of blood pressure with visceral fat has a coefficient of 0.14 which indicates a moderate relationship. The correlation of systolic and visceral fat (r = 0.350) showed a low relationship, while the correlation of diastolic and visceral fat (r = 0.416) showed a moderate relationship. The most patients diagnosed with type 2 DM at Haji Medan Hospital are male with a percentage of 53.6% with the highest age range of 50-59 years, there is a positive correlation between the percentage of visceral fat and blood pressure, both systolic and diastolic.